Islamic Values in English Learning - Yuliana, Wahidah (JADEs Journal of Academia in English Education, 2021)
The purposes of this study are to analyze how the English learning materials are provided by an English teacher and what moral values are contained in English learning materials to improve students’ interest in learning English. To achieve the purposes of this study, the researcher used qualitative approach with case study type by taking place at MAS Nurul fata and data collection techniques are observation and interview with an English teacher and four students at the tenth grade students of MAS Nurul Fata. The data analysis in this study used Miles and Huberman framework. The result of this research showed that the English learning materials provided by teacher to the tenth-grade students are narrative text, announcement text and expressing an invitation. The moral values are contained in narrative text material are morals toward Allah in the form resignation, patience and sincere. The moral values are contained in announcement text material are moral toward environment in the form always clean and beautify the environment. The moral value is contained in expressing an invitation is moral toward fellow humans in the form hospitality.